Methodological test for the automated characterization of metallic ores by means of image digital analysis. Geometallurgical application - Pérez Barnuevo, Laura (2012)
The equipment of DIA is composed by a refl ection microscope, a video camera 3CCD, a frame grabber and the analysis image software. All these elements are interrelated so that the scenes visualized in the microscope are captured by the video camera and digitized and stored in the computer, where, through the analysis image software they will be processed to obtain the necessary information. The methodology to be tested is the one developed by E. Berrezueta (2004), in the Laboratory of Applied Microscopy of the Superior School of Mines, Madrid, where the present work has been carried out. The above mentioned methodology describes the necessary steps to achieve the adjustment of the equipment of DIA, that is to say, to reach the necessary conditions of stability to obtain reliable and reproducible results. One of the above mentioned conditions are reached, the validity of the method will be tested by means of its application to the mineral quantifi cation of polished samples studied before by an expert mineralogist, and quantifi ed by the traditional method of the points counter operator.